Answer:
f(g(x)) = 2(x^2 + 2x)^2
f(g(x)) = 2x^4 + 8x^3 + 8x^2
Step-by-step explanation:
Given;
f(x) = 2x^2
g(x) = x^2 + 2x
To derive the expression for f(g(x)), we will substitute x in f(x) with g(x).
f(g(x)) = 2(g(x))^2
f(g(x)) = 2(x^2 + 2x)^2
Expanding the equation;
f(g(x)) = 2(x^2 + 2x)(x^2 + 2x)
f(g(x)) = 2(x^4 + 2x^3 + 2x^3 + 4x^2)
f(g(x)) = 2(x^4 + 4x^3 + 4x^2)
f(g(x)) = 2x^4 + 8x^3 + 8x^2
Hope this helps...
Answer:
The equation that represents the graph is y = 40x
The new equation would be y = 45x
Step-by-step explanation:
As y increases by 40, x increases by 1, so 40/1, or 40
New equation: $90 per 2 months, y = 90, x = 2, 90/2 = 45
The angles inside a trapezoid add up to equal 360 degrees
X = 360-90-90-75 = 105 degrees.
Try Using the Formula I=Prt
principal×rate×time
so
P-1200
R-.039
T-8 months
Step-by-step explanation:
Does this help?